Peripheral milling force induced error compensation using analytical force model and APDL deformation calculation. Issue 9 (February 2017) - Du, Zhengchun; Zhang, Di; Hou, Hongfu; Liang, Steven
Abstract Milling low-rigidity and flexible parts is a common and challenging process in the aerospace and aeronautics industry, and the cutting force induced deformation is one of the most important parts of all the error sources. In this paper, a precise and economical cutting force induced error compensation method for both low-rigidity parts and other complex components based on a generalized explicit analytical milling force model and a fast ANSYS parametric design language (APDL) deformation calculation procedure is proposed for peripheral milling process. First, a peripheral milling force model is set up according to the shearing mechanism and the plowing mechanism on the basis of Fourier series. Then, through superposition and Fourier transformation in angle domain, the predictive model of peripheral milling forces is established, which simplifies the calculation compared with other empirical or analytical methods. Based on the above force model, a generalized milling force induced deformation calculation procedure based on the fast APDL method is introduced. Therefore, the surface dimensional error of the flexible thin-wall structure can be rapidly predicted and further be compensated by optimizing the tool path off-line. Finally, experiments were performed over various cutting conditions. The results verify the fidelity and applicability of this method for low-rigidity thin-wall part milling process. It also shows great potential in the application of real-time milling force induced error compensation.